Investigation on Tribological and mechanical behaviour of AA6082—Graphene based composites with Ti particles. (17th July 2020) - Rajaganapathy, C; Vasudevan, D; Selvakumar, N
Abstract: In the recent years, high strength and low weight materials are being preferred in automobile sectors for fabricating high-speed rotating shafts and machineries. For satisfying dynamic requirements, Aluminium Metal Matrix Composites can be used. In this paper, an attempt has been made to fabricate AA 6082—graphene based Aluminium Matrix Composites reinforced with Titanium (Ti) particles. The effect of increase weight percentage of Graphene and Ti reinforcement on the mechanical characteristics was evaluated. Using tensile tests and surface micro hardness measurements, the fluctuations in mechanical aspects were measured. Tribological characteristics of the Aluminium Matrix Composites were found using pin on disc tribo wear meter, using Silver (Ag) nanoparticles incorporated Jatropha oil as bio-lubricant. Microstructural variations were evaluated by using FESEM which indicated surface tear offs, surface ploughing, demarcations, micro pits, grooves, demarcations, micro cuts and micro tears on the surfaces. The effect of Ag Nano particle addition on Jatropha oil was observed with the fluctuations in Coefficient of friction, specific wear rate and wear mass loss. On increase in reinforcement percentage of G and Ti, specific wear rate was found to decrease and coefficient of friction decreased till 3% by weight reinforcement and beyond 3%, it increased. The surface chemistry modifications were identified using XRD. It was observed that AA6082 Aluminium Matrix Composites reinforced with 3% G and 3% Ti exhibited better mechanical and tribological properties when used with 1% Ag Nanoparticles incorporated Jatropha oil as lubricant.